Flexoelectric polarization studies in bent-core nematic liquid crystals - Vij, Jagdish; Panarin, Yuri (My University, 2015)
The flexoelectric polarization ( P f ) of four bent-core nematic liquid crystals (LCs) has been measured using the pyroelectric effect. Hybrid aligned nematic cells are fabricated for measuring the pyroelectric response over the entire range of the nematic phase. It is found that the magnitude of flexoelectric polarization P f and the sum of the flexoelectric coefficients | e 1 + e 3 | for the bent-core LCs studied here are three to six times higher than for the calamitics. P f is found to depend on the transverse dipole moment of LC molecules. However, | e 1 + e 3 | values are by no means giant as | e 3 | alone had been reported for a bent-core nematic system previously. The dependence of the sum of “splay and bend flexoelectric coefficients” is discussed in terms of the shape of the molecule and of the dipole moment directed normal to the molecular axis.
PUBLISHED
DOI: 10.1103/PhysRevE.92.022502
Keywords: flexoelectric polarization; flexoelectric polarization